Diffusion in a Random Velocity Field: Spectral Properties of a Non-Hermitian Fokker-Planck Operator - Chalker, J; Wang, Z (1997)
We study spectral properties of the Fokker-Planck operator that describes particles diffusing in a quenched random velocity field. This random operator is non-Hermitian and has eigenvalues occupying a finite area in the complex plane. We calculate the eigenvalue density and averaged one-particle Green's function, for weak disorder and dimension d>2. We relate our results to the time-evolution of particle density, and compare them with numerical simulations.